Analysis of Tourism Development Potential on Bawean Island - Samwil, Samwil; Ciptadi, Gatot; Marjono (Graduate School of Universitas Brawijaya, 2026)
The purpose of this study is to determine the potential for the development of Bawean Island tourism. Research methods used was qualitative with a case study approach. This research data was obtained from the results of observations, interviews and documentation which related to the development of tourism in Bawean island. The results showed that the potential for the development of Bawean Island tourism can be seen from the existence of local and foreign visitors reaching 178.235 visitors in 2022, indicating that Bawean Island has the potential for diversification of tourism products, the availability of land and marine transportation access and the existence of policies and regulations that make Bawean Island as a zone tourism development priority. Because the findings of this research are identified qualitatively, it is recommended in further studies to conduct quantitative analysis so significantly the influence of the potential development of Bawean Island tourism can contribute and support sustainable tourism development.